PENERAPAN METODE KURABA MOLEKUL UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MATERI TATA NAMA SENYAWA KARBON - Subagiyo, Sidiq (Sains and Technology Faculty, Walisongo State Islamic University, 2018)
This study aims to determine whether (1)Â The application of Kuraba Moleculelearning method is able to increase learning activity and (2) Application of learning method Kuraba Molecule is able to improve cognitive learning result. The research method used is classroom action research consisting of two cycles. The subjects of this study were students of class XI IPS SMA Negeri 1 Lasem Lesson Year 2016 / 2017. In this research, the Sample is taken using technique Purposive Sampling. The sample is class XI IPS 4. Research data in the form of cognitive learning outcomes and learning activities. Data collection is done through observation, test, questionnaire, and documentation. The quantitative descriptive analysis is used to analyze the data. The results of the research and analysis show that: (1) Application of Kuraba Molecule learning methods is able to improve student learning activities. The activeness of students before the action of 30.3%, in the first cycle, increased to 57.58%, and in the second cycle increased to 84.84%. (2) Application of Kuraba Molecule learning method is able to improve student cognitive learning outcomes. The classical completeness before the action was 27.27%, in the first cycle increased to 66.67%, and in the second cycle increased to 78.78%.